MicroRNA-665 and its potential role in drug response and survival outcomes in multiple myeloma: a preliminary study - Bergantim, Rui; Peixoto da Silva, Sara; Pinto, Vanessa; Pereira, Joana M.; Sousa, Diana; Trigo, Fernanda; Matthiesen, Rune; Guimarães, José E.; Vasconcelos, M. Helena (Frontiers in Pharmacology, 2025)
BackgroundMultiple myeloma (MM) is a complex hematological malignancy with heterogeneous clinical and pathophysiological backgrounds that influence treatment responses and outcomes. Identifying biomarkers to predict drug response and guide treatment decisions, particularly regarding drug combinations, is essential to improve therapeutic efficacy and patient outcomes. This study explores the role of microRNAs (miRNAs/miRs) derived from bone marrow (BM) and peripheral blood (PB) in responses to treatment and survival outcomes in newly diagnosed MM (ndMM) patients.MethodsThis study included twenty patients with ndMM undergoing first-line treatment with bortezomib, thalidomide, and dexamethasone. The miRNAs were isolated from BM and PB, and their profiles were analyzed using Next-Generation Sequencing (NGS), followed by validation of differentially expressed miRNAs by quantitative real-time PCR (qPCR). Clinical and response data were collected to assess correlations between miRNA levels, clinical characteristics, and patient outcomes. In silico analysis for target-prediction and gene ontology (GO) enrichment was performed to explore the potential biological and functional role of the identified miRNAs.ResultsNGS profiling revealed several miRNAs differently expressed between treatment-refractory and sensitive patients, as well as between PB and BM. Among these, miR-665, miR-483-5p, miR-143-3p and miR-145-5p were selected for further validation by qPCR. It was observed that miR-665 was significantly elevated in treatment-refractory patients compared to treatment-sensitive patients. Additionally, miR-665 levels were higher in PB than in BM. Elevated miR-665 levels were associated with more aggressive disease characteristics and poorer clinical outcomes, including reduced overall survival.DiscussionOur preliminary findings suggest that miR-665 could potentially serve as a non-invasive tool for predicting drug resistance and guiding treatment decisions in MM. These findings also highlight the potential utility of miRNAs in liquid biopsies as a predictive tool of drug response in MM and could pave the way for personalized treatment strategies, improving patient outcomes. Future research is needed to validate these results in larger cohorts and explore the underlying mechanisms of miR-665 in MM pathogenesis and drug resistance.